Volumetric Behavior of Oil and Gas from the Rio Bravo Field - B. H. Sage (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1940)
ATTEMPTS have been made to predict the volumetric and phase behavior of naturally occurring hydrocarbon mix-tures1-5 but these methods have not been extended to the higher pressures and tem-peratures that are currently encountered in some producing formations. Furthermore, the methods of prediction at present avail-able have not been tested in a sufficient number of cases to ensure their applica-bility to all naturally occurring hydrocar-bon mixtures, even at the lower pressures and temperatures. For these reasons the behavior of a number of hydrocarbon mix-tures from a field in which the subsurface pressures are above 4500 lb. per sq. in.? and the temperatures are in the neighbor-hood of 250°F. was investigated.